‘Who is going to explain it to me so that I understand?’: health care needs and experiences of older patients with advanced heart failure - Gerlich, Miriam G.; Oster, Peter (European journal of ageing, 2012)
Heart failure is a leading cause of death and can result in significant palliative care needs. The aim of this study was to explore the needs of older patients with advanced heart failure, and their experiences with health care delivery in Germany. Qualitative interviews were carried out with 12 patients (6 men, 6 women; age 73-94 years; heart failure in an advanced stage according to the New York Heart Association Functional Classification) recruited in two geriatric hospitals. The interviews were analyzed by a qualitative descriptive approach. The main categories derived from the patient interviews were: understanding of illness and prognosis, health care services and social life. The patients expressed the need for better information and communication regarding illness and prognosis, and the desire for more respectful treatment by health care providers. Heart failure was not recognized as a potentially life-limiting disease, and the patients had no experience with palliative care services. The study emphasizes the need for improving communication with patients with advanced heart failure. To achieve this, strengthening the palliative care approach in all relevant services that deliver care for these patients and introducing advanced care planning appear to be promising strategies.
Gesehen am 07.05.2018